Influence of the metal salt on the self-assembly of isophthaloylbis-β-alanine and Cu(II) ion. (29th March 2015) - Lymperopoulou, Smaragda; Dokorou, Vassiliki N.; Tsipis, Athanassios C.; Weidler, Peter G.; Plakatouras, John C.; Powell, Annie K.; Kostakis, George E.
Graphical abstract: The employment of isophthaloylbis-β-alanine (H2 IBbA, H2 L) with Cu(II) ion affords two compounds [Cu2 L2 (H2 O)(CH3 OH)]·2H2 O·CH3 OH (1 ) and [Cu2 L2 (H2 O)4 ]·6H2 O (2 ), illustrating the important influence of the metal salt and the solvent system used in determining the motif of the final product. Abstract: The initial employment of the new pseudopeptidic ligand isophthaloylbis-β-alanine (H2 IBbA, H2 L) with Cu II ion affords a one dimensional (1D) [Cu2 L2 (H2 O)(CH3 OH)]·2H2 O·CH3 OH (1 ) and a two dimensional (2D) [Cu2 L2 (H2 O)4 ]·6H2 O (2 ) compound, respectively, illustrating the important influence of the metal salt and the solvent system used in determining the motif of the final product. Infrared spectroscopy, thermal, adsorption and theoretical studies of these compounds are also discussed.